PROBLEM OF SUPER-STRONG MAGNETIC FIELDS ON THE SUN: BRIEF CHRONOLOGY AND NEW OBSERVATIONAL DATA - Lozitsky, V. G.; Yurchyshyn, V. B.; Ahn, K.; Wang, H.; Lozitska, N. I. (Одеські астрономічні публікації, 2018)
In this study we present the old and new observational data concerning the problem of extreme magnetic fields (  5 kG) in the Sun’s atmosphere. We emphasize that the upper limit of the intensity of the magnetic field in the solar atmosphere is unknown to date. Severny (1957) heuristically suggested that the magnetic fields in the sunspots could reach 50 kG. As for the observational data, at least three arguments in favor of the magnetic fields of the order of 104 G can be specified: (1) the dependence of the measured magnetic field on the factor geff2 of magnetosensitive lines (Gopasyuk et al., 1973; Lozitsky, 1980), (2) local extremums in splitting of bisectors in the profiles I ± V for lines with different Lande factors (Lozitsky, 1980; 2015) and (3) the reliable splitting of emission peaks in Fe I lines with very low Lande factors, about 0.01, in the spectra of powerful solar flares (Lozitsky, 1993; 1998). Theoretically, superstrong fields should have gigantic magnetic pressure and can exist only with a specific topology of field lines, apparently of a force-free type (Soloviev and Lozitsky, 1986). To further develop this problem, we are analyzing new observational data obtained with the NIRIS spectropolarimeter of the largest GST solar telescope of the Big Bear Solar Observatory (BBSO). Our observations relate to the active region NOAA 12673, which was the most flare-productive in the 24th cycle. Stokes-metric measurements are made in the FeI 15648.5 Е line with a signal-to-noise ratio of about 10-4. In this active region, superstrong magnetic field of 5.57 kG was discovered recently by Wang et al. (2018). An additional study of about 70 different places in this active region suggested that there were two types of places that can be conventionally called "typical" and "peculiar". In "typical" areas, the magnitude of the magnetic field in general is the greater, the less the intensity in the spectral continuum, and the maximum field here does not exceed 4 kG. All "peculiar" places correspond to positions with the highest intensity in the spectral continuum, and the magnetic field strength is here in the range of 3.0-5.7 kG. Notice, such strong magnetic fields were firstly discovered outside the sunspot umbra. The orientation of the magnetic field vector in "peculiar" places is close to the transversal, which is also atypical for "typical" regions and can reflect strong twisting of field lines.